FORAMINIFERAL AND TEXTURAL CHARACTERISTICS OF WELL X, EASTERN NIGER DELTA: IMPLICATIONS FOR PALEOENVIRONMENTAL RECONSTRUCTION - Adeyokun, Adenike; Ayeniyo, Olutayo; Opeloye, Saka (FUDMA Journal of Sciences, 2026)
Foraminiferal and textural analyses were conducted on sediments from 1320–4230 m in Well X, offshore eastern Niger Delta, to refine paleoenvironmental interpretation within a stratigraphic framework. The assemblages range from barren to moderately rich, with the identification of the NNDf 05 benthic foraminiferal zone supporting a Miocene age. The dominance of environmentally diagnostic benthic forms indicates deposition under reduced oxygen, relatively quiet marine conditions. Textural observations of interbedded shale, silty shale, and sandstone, combined with foraminiferal assemblages, indicate a middle to outer neritic setting. Vertical variations in lithofacies and faunal composition reveal a gradual upward shift toward more proximal, higher-energy shelf conditions. This approach shows how combining foraminiferal and sediment data improves depositional and stratigraphic interpretation in the Niger Delta.